Protocol for neurogenin-2-mediated induction of human stem cell-derived neural progenitor cells - Ellen J. Guss; Laila Sathe; Alexander Dai; Tim Derebenskiy; Ana Rodriguez Vega; Kevin Eggan; Michael F. Wells (STAR Protocols, 2024)
Summary: Human pluripotent stem cell-derived neural progenitor cells (NPCs) are an essential tool for the study of brain development and developmental disorders such as autism. Here, we present a protocol to generate NPCs rapidly and reproducibly from human stem cells using dual-SMAD inhibition coupled with a brief pulse of mouse neurogenin-2 (Ngn2) overexpression. We detail the 48-h induction scheme deployed to produce these cells—termed stem cell-derived Ngn2-accelerated progenitor cells—followed by steps for expansion, purification, banking, and quality assessment.For complete details on the use and execution of this protocol, please refer to Wells et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.